2018
DOI: 10.18805/ijar.b-1058
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prevalence of Fasciola hepatica and associated biochemical alterations in the cattle of Siirt province, Turkey

Abstract: The aim of this study is to determine the prevalence of Fasciola hepatica in the cattle raised in the Siirt province of Turkey and to obtain epidemiologic data about the disease in order to reveal its relationship with certain biochemical parameters. The material of the study consists of a total of 380 cattle. The blood sample was obtained from the jugular vein of the animals. Meanwhile, approximately 50-100 gr of feces were also collected from the animal’s rectum for a fecal examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Although the current study outcome was lower than the rates obtained in Iran, which was 32% 37 . In contrast, the prevalence was lower than 7.5 % reported in Turkey 38 .…”
Section: Epidemiological Studycontrasting
confidence: 67%
“…Although the current study outcome was lower than the rates obtained in Iran, which was 32% 37 . In contrast, the prevalence was lower than 7.5 % reported in Turkey 38 .…”
Section: Epidemiological Studycontrasting
confidence: 67%
“…(Rahman et al, 2017). The odds of fascioliasis positivity in female goats and sheep was 2.7918 times (95% CI: 1.7314-4.5017, P < 0.05) and 3.7317 times (95% CI: 1.7314-4.5017, P < 0.05) respectively than male goats and sheep which is higher compared to the level of odds obtained in previously published reports (Aktaruzzaman et (Çelik Ö and Aslan Çelik, 2018). This study also revealed that there was a signi cant association between body condition score and fascioliasis in sheep and goats.…”
Section: Prevalence Of Fascioliasis In Slaughtered Sheepmentioning
confidence: 53%
“…The liver fluke of the genus Fasciola is an extremely pathogenic parasite that affects humans and animals and causative agent of fascioliasis ( 1 ). Animal liver infection with Fasciola species results a large economic loss ( 2 ). This trematode directly affects livestock productivity through host mortality (in sheep) and partial or complete liver condemnation.…”
Section: Introductionmentioning
confidence: 99%